Pemanfaatan Keanekaragaman Tumbuhan Untuk Pembuatan Batik Ecoprint di Desa Sidomulyo, Yogyakarta - Oktira Roka Aji; Ambar Pratiwi; Nursyiva Irsalinda (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2023)
Many villages face challenges in optimizing their local potential. Sidomulyo Village, Bambanglipuro, Bantul, is one of the villages with abundant natural resources, including diverse plant species that have not been fully utilized. To address this, a community engagement program has been designed to provide training on the utilization of plant diversity in Sidomulyo Village for creating ecoprint batik fabric. The method employed in this community engagement program involves training in ecoprint creation using natural dyes and various local plant leaves. Throughout the program's implementation, the activities have been successful and have yielded positive outcomes. Participants' knowledge about ecoprint has increased significantly, from 20% to 100%. The enthusiasm of the participants in participating in the ecoprint training has been remarkable. Beyond the knowledge enhancement, many participants have shown an interest in further developing ecoprint variations, and some are even keen on establishing ecoprint businesses. Through this program, it is hoped to stimulate the growth of the creative economy by harnessing the natural potential within the surroundings of Sidomulyo Village. All of these efforts contribute to the improvement of the well-being and empowerment of the local community.